A theoretical and experimental study of piezoelectric microdiaphragm platforms for physical and biological sensing - Mohammad Olfatnia (2012)
This thesis reports theoretical and experimental study of piezoelectric microdiaphragm platform for physical and biological sensing. The microdiaphragms were first designed and then fabricated by MEMS fabrication processes. Their different characteristics such as frequency behavior, mode shapes, coupling factor, quality factor (Q-factor), nonlinear vibrations, mass sensitivity, and pressure sensitivity were studied theoretically and experimentally. Finally, they have been applied for two different schemes of sensing; mass sensing and pressure sensing. These experimental results demonstrate promising perspective of piezoelectric microdiaphragms as physical and chemical sensors.